2017
DOI: 10.2224/sbp.6754
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' perceived parental psychological control and test anxiety: Mediating role of academic self-efficacy

Abstract: We examined the relationship between parental psychological control and their children's test anxiety in the Chinese cultural context, and tested the mediating role of the children's academic self-efficacy in this relationship. Chinese high-school students (N = 401, 158 boys and 243 girls), aged between 15 and 18 years, completed a self-report survey assessing parental psychological control, academic self-efficacy, and test anxiety. The results showed a positive association between parental psychological cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 6 publications
2
14
0
Order By: Relevance
“…The higher the score, the stronger the sense of ASE. This scale demonstrated good reliability and validity in previous studies (Liang, 2000;Shi et al, 2013;Xu et al, 2017). In the present study, the Cronbach's alpha coefficients of the Academic Competence Efficacy Subscale and the Academic Behavior Efficacy Subscale were 0.92 and 0.70, respectively.…”
Section: Academic Self-efficacy Scalesupporting
confidence: 78%
“…The higher the score, the stronger the sense of ASE. This scale demonstrated good reliability and validity in previous studies (Liang, 2000;Shi et al, 2013;Xu et al, 2017). In the present study, the Cronbach's alpha coefficients of the Academic Competence Efficacy Subscale and the Academic Behavior Efficacy Subscale were 0.92 and 0.70, respectively.…”
Section: Academic Self-efficacy Scalesupporting
confidence: 78%
“…The findings concurred with previous studies that found that maternal pressure reduced adolescents' sense of self-efficacy [10] as well as English anxiety [13]. Also, the paper confirmed the study that academic self-efficacy had a partial mediating role on parental psychological control and test anxiety [15]. The results are in a similar context to the results of the previous studies that reported a negative relation between English self-efficacy and English anxiety in elementary school students [17], as well as a negative association between English writing self-efficacy and English writing anxiety among middle school students [18].…”
Section: Discussionsupporting
confidence: 91%
“…Previous research [14] suggested that strategies on cognitive and behavioral regulation, such as organization and seeking peer assistance, had a significant impact on students' verbal efficacy, leading to the proposal that self-directed learning influences English self-efficacy. Moreover, a higher sense of parenting control could have a harming effect on academic self-efficacy [15] by increasing anxiety arousal [16]. From studies conducted in Korea, English self-efficacy was considered as an important factor in explaining English anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies used self-developed measures [ 32 , 71 , 72 , 73 , 74 ]. Regarding the adaptation of measures among the included studies, thirty-one studies used translated measures [ 18 , 20 , 22 , 25 , 26 , 32 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 58 , 59 , 60 , 61 , 63 , 64 , 65 , 67 , 68 , 69 , 70 , 75 ], ten used non-translated measures [ 21 , 23 , 28 , 29 , 33 , 66 , 71 , 72 , 73 , 74 ], and two of them used both translated and non-translated measures [ 32 , 62 ]. The psychometric properties of the measures, such as validity and reliability, can be retrieved in each study included in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%